Development and delivery cost of digital health technologies for mental health: Application to the Narrative Experiences Online Intervention - Paterson, Luke; Rennick-Egglestone, Stefan; Gavan, Sean P.; Slade, Mike; Ng, Fiona; Llewellyn-Beardsley, Joy; Bond, Carmel; Grundy, Andrew; Nicholson, Joe; Quadri, Dania; Bailey, Sylvia; Elliott, Rachel A. (Frontiers in Psychiatry, 2022)
Background: The increasing development and use of digital health interventions requires good quality costing information inform development and commissioning choices about resource allocation decisions. The Narrative Experiences Online (NEON) Intervention is a web-application that delivers recorded mental health recovery narratives to its users. Two randomized controlled trials are testing the NEON Intervention in people with experience of psychosis (NEON) and people experiencing non-psychosis mental health problems (NEON-O). Aim: This study describes and estimates the cost components and total cost of developing and delivering the NEON Intervention. Materials and Methods: Total costs for the NEON Trial (739 participants) and NEON-O Trial (1,024 participants) were estimated by: identifying resource use categories involved in intervention development and delivery; accurate measurement or estimation of resource use; and a valuation of resource use to generate overall costs, using relevant unit costs. Resource use categories were identified through consultation with literature, costing reporting standards and iterative consultation with health researchers involved in NEON Intervention development and delivery. Sensitivity analysis was used to test assumptions made. Results: The total cost of developing the NEON Intervention was £182,851. The largest cost components were software development (27%); Lived Experience Advisory Panel workshops (23%); coding the narratives (9%); and researchers’ time to source narratives (9%). The total cost of NEON Intervention delivery during the NEON Trial was £118,663 (£349 per NEON Intervention user). In the NEON-O Trial, the total delivery cost of the NEON Intervention was £123,444 (£241 per NEON Intervention user). The largest cost components include updating the narrative collection (50%); advertising (19%); administration (14%); and software maintenance (11%). Uncertainty in the cost of administration had the largest effect on delivery cost estimates. Conclusion: Our work shows that developing and delivering a digital health intervention requires expertise and time commitment from a range of personnel. Teams developing digital narrative interventions need to allocate substantial resources to curating narrative collections. Implications for Practice: The NEON Intervention is intended for widespread use as a low-cost self-management intervention. These findings will inform decision-making about the costs of delivering the NEON Intervention and other mental health digital health interventions at scale.